SEMINAR TEKNIK BUDIDAYA PERAIRAN BAGI PENGEMBANGAN USAHA PRODUKTIF DI PAPUA NUGINI - Pattipeiluhu, Shelly (Universitas Mataram, 2024)
Aquaculture is a mean of raising fish in rivers, ponds, lakes, and sea environments under control for a specific time with the intention of harvesting. However, this aquaculture activity is not widely known in South Pacific countries, especially in Papua New Guinea. Recognizing the significance of aquaculture for possible community economic development, some members affiliated with the Men’s University of Papua New Guinea Congregation have taken the initiative to undergo training on aquaculture. The objectives of this activity is to provide a basic understanding of aquaculture for community groups technically and to enhance skills for engaging in productive entrepreneurship in fish farming. The activity attended by 53 active participants, including community members, academic staff, students and practitioners, followed by a discussion. To deepen their knowledge and skills, participants underwent assessments in the form of questionnaires. The seminar activities resulted in 63.5% of participants having a very good understanding of aquaculture technology and the economic aspects with values between 55-75%. Understanding of 'aquaculture' reached a value of 75%, and 'types of aquaculture that can be developed in PNG' was 66%, both above the target. Based on the sufficient understanding of aquaculture and the outcome of the activity, two participants were selected to attend internships at the training centers in Indonesia. This community service activity is highly beneficial for small community groups and expected to serve as an embryo for the development of aquaculture enterprises in Papua New Guinea, especially within the grassroots community.